2014
DOI: 10.1038/cdd.2014.147
|View full text |Cite
|
Sign up to set email alerts
|

Cell type-specific Nogo-A gene ablation promotes axonal regeneration in the injured adult optic nerve

Abstract: Nogo-A is a well-known myelin-enriched inhibitory protein for axonal growth and regeneration in the central nervous system (CNS). Besides oligodendrocytes, our previous data revealed that Nogo-A is also expressed in subpopulations of neurons including retinal ganglion cells, in which it can have a positive role in the neuronal growth response after injury, through an unclear mechanism. In the present study, we analyzed the opposite roles of glial versus neuronal Nogo-A in the injured visual system. To this aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 61 publications
0
47
1
1
Order By: Relevance
“…We have previously reported that glia-specific inactivation of Nogo-A increased retinal ganglion cell plasticity after optic nerve injury (Vajda et al, 2015) and after monocular deprivation in intact animals (Guzik-Kornacka et al, 2016). In the brain, the Nogo-A-S1PR2 ligandreceptor pair may also operate in the mechanisms controlling blood vessel plasticity after stroke.…”
Section: Discussionmentioning
confidence: 97%
“…We have previously reported that glia-specific inactivation of Nogo-A increased retinal ganglion cell plasticity after optic nerve injury (Vajda et al, 2015) and after monocular deprivation in intact animals (Guzik-Kornacka et al, 2016). In the brain, the Nogo-A-S1PR2 ligandreceptor pair may also operate in the mechanisms controlling blood vessel plasticity after stroke.…”
Section: Discussionmentioning
confidence: 97%
“…15 Severed RGC axons, such as the spinal cord long tracts, have no capacity to regenerate under normal physiological circumstances. This is due to the virtually ubiquitous presence of factors that inhibit axon regeneration, such as Nogo, chondroitin sulfate proteoglycan (CSPG), and myelinassociated glycoprotein (MAG).…”
Section: Inhibition Of Optic Nerve Axon Regenerationmentioning
confidence: 99%
“…This is due to the virtually ubiquitous presence of factors that inhibit axon regeneration, such as Nogo, chondroitin sulfate proteoglycan (CSPG), and myelinassociated glycoprotein (MAG). 15 Similarly, although axons of embryonic RGCs can grow axons into the superior colliculus, RGC axons of postnatal animals fail to extend into CNS tissue, even when it is derived from the embryonic tectum. 16 Thus, the failure to reestablish vision is a multifactorial phenomenon:…”
Section: Inhibition Of Optic Nerve Axon Regenerationmentioning
confidence: 99%
“…Both MLC II and cofilin can also be regulated through the RhoA/ROCK pathway and respectively result in actomyosin contraction and F-actin depolymerization, then inducing growth cone retraction [53]. Nogo-A-D20 interacts with S1PR2 and maybe some other unidentified receptors and inactivates CREB that regulates the transcription of target genes as well as dephosphorylates F-actin and activates ROCK [18,83,115]. Other proteins such as FGF-2 also interact with NgR1, resulting in the inhibition of FGF-2's binding to its receptor [99,100].…”
Section: Migration and Distributionmentioning
confidence: 99%
“…In addition,in the sensory DRG neurons, the Nogo-66 receptor homolog NgR2, a member of the Nogo-66 receptor NgR family which consists of three structurally related proteins called NgR1-3, also shows its potent effect on the epidermal innervation by interacting with versican which may synergize with Nogo-A as a repellent factor to sensory axons [56,81,82]. Additionally, a recent on-line published work reveals that neuronal Nogo-A in retinal ganglion cells could participate in enhancing axonal sprouting, possibly by cis-interaction with Nogo receptors at the cell membrane that may counteract trans-Nogo-A signaling [83]. This study suggests that inactivating Nogo-A in glia while preserving neuronal Nogo-A expression may be a successful strategy to promote axonal regeneration in the CNS.…”
Section: Migration and Distributionmentioning
confidence: 99%